CPEB3 Maintains Developmental Competence of the Oocyte - Lamacova, Lucie; Jansova, Denisa; Jiang, Zongliang; Dvoran, Michal; Aleshkina, Daria; Iyyappan, Rajan; Jindrova, Anna; Fan, Heng-Yu; Jiao, Yuxuan; Susor, Andrej (Cells, 2024)
Mammalian oocyte development depends on the temporally controlled translation of maternal transcripts, particularly in the coordination of meiotic and early embryonic development when transcription has ceased. The translation of mRNA is regulated by various RNA-binding proteins. We show that the absence of cytoplasmic polyadenylation element-binding protein 3 (CPEB3) negatively affects female reproductive fitness. CPEB3-depleted oocytes undergo meiosis normally but experience early embryonic arrest due to a disrupted transcriptome, leading to aberrant protein expression and the subsequent failure of embryonic transcription initiation. We found that CPEB3 stabilizes a subset of mRNAs with a significantly longer 3'UTR that is enriched in its distal region with cytoplasmic polyadenylation elements. Overall, our results suggest that CPEB3 is an important maternal factor that regulates the stability and translation of a subclass of mRNAs that are essential for the initiation of embryonic transcription and thus for embryonic development.
Keywords: proteiny vázající RNA; stabilita RNA; messenger RNA; embryonální vývoj; Polyadenylation; 3' nepřekládaná oblast; Female; 3' Untranslated Regions; Meiosis; zvířata; myši; Mice; oocyty; Gene Expression Regulation, Developmental; meióza; RNA, Messenger; Embryonic Development; polyadenylace; ženské pohlaví; RNA Stability; vývojová regulace genové exprese; Animals; Oocytes; RNA-Binding Proteins